Zeszyt kontaktów jako narzędzie komunikacji szkolnej - Szczerbińska, Barbara (Dydaktyka Polonistyczna, 2017)
The most important features in education process are effective communication, exchange ofinformations between school and parents about student’s progress, organizational and tutelary- educational matters. The subject of article considers speculations about structure, style and pragmaticaspect of inscriptions put in issue notebook as the matter of communication between teacher andthe student’s family home. Four notebooks, which were shared by the parents for the purposes ofthis research paper, were elaborately analysed. To the fore of interaction between the teacher andstudent’s home environment come such forms of linguistic behaviours which may be considered ascomplaints, questions or requests. Some of them sound like charges, regrets over one’s behaviourand proceeding. Parents also occur in the role of the sender- they write justifications or excusals fromclasses if needed. The most common forms of language are in official and elevated style.